The Evolution of the Vicious Cycle in Thai Politics: From 1932 to the Period of General Prayut Chandra-ocha - Kaewmanee, Dhiwakorn (Journal of Social Sciences Naresuan University, 2025)
This research focuses on the repetitive occurrences of coup d’etat as a driving force in Thailand’s political development, which might be seen as a vicious cycle. The research’s main question is whether the vicious cycle model is just a theoretical concept or an empirical political phenomenon. The research also answers if the vicious cycle is still apparent throughout the changes in contemporary Thai politics? This study has been conducted with the combination of document research and qualitative research of participant and non-participant observations. Study results show that coup is still considered as an integrated event in the unique political development of the Thai state, which appears to happen in cycles. The cycle can be described with an order of events that follows this basic flow: starting with conflict, political crises, coups, and military rule; followed by drafting a constitution to restore power to the people; holding elections and installing new government, that again are likely to experience new conflict, crisis, and coups. The research concludes that the political changes in the Thai state since 1932 have been followed according to this model, with the coup at the heart of the vicious cycle. While the cycle slowed and even paused for around fifteen years during the semi-democratic period arising in the 1980s. However, the latest coup led by General Prayut has once again confirmed that the coup remains at the heart of changes in the Thai state and the driving force of the system, which evidently leads to the result of the vicious cycle being an empirical phenomenon in the Thai state.